Traumatic adrenal haemorrhage : a case report - Che Mohamed, Siti Kamariah; Abdul Rashid, Mohd Amran; S, Sharini; J, Khairussaleh (2009)
Introduction: Adrenal injuries are rare, as the adrenal glands lies deep in the abdomen, seemingly protected from blunt abdominal trauma. Computed tomography(CT) is the gold standard for evaluating adrenal gland injuries, where haematoma and active bleeding due to injury to the suprarenal vessels may be visualized using new multi-detector row CT (MDCT). The prevalence of adrenal haemorrhage among patients with blunt abdominal trauma undergoing CT scanning is 2%, among which 60% occur on the right side, 25% on the left and 15% are bilateral. Depending on the extent of the injury and the patients haemodynamic stability, adrenal haemorrhage is addressed surgically or conservatively.